Self-Efficacy Approach Through Social Cognitive in Enhancing Knowledge About Hypoglycemia Preventionin Diabetes Mellitus Patients Year 2023 - Zakariyati, Zakariyati; Alamsyah, Alamsyah (Viva Medika, 2023)
Hypoglycemia is a more dangerous problem for people with diabetes mellitus if it is not detected or prevented by the sufferer. Health education based on cognitive theory is an alternative to strengthen the self-efficacy of DM sufferers to increase knowledge of hypoglycemia prevention. This study aims to determine the effect of cognitive theory with a self-efficacy approach to increasing knowledge about the prevention of hypoglycemia in patients with diabetes mellitus. This research method is Quasi Experiment with one group pre test post test design. The number of samples for this research was 55 people using purposive sampling. The intervention in this research is health education with a social cognitive theory approach. The results of this study showed that there were differences in the results of the pre-test and post-test of knowledge about preventing hypoglycemia in 55 respondents with a mean (pre-test 17.82 and post-test 22.15). The results of the t test show the sig. p 0.00< 0.05. The conclusion is that there is an influence of cognitive theory with a self-efficacy approach to increasing knowledge about the prevention of hypoglycemia in patients with diabetes mellitus. The best suggestion for future research is the need for patient self-efficacy control to increase patient knowledge on the prevention of hypoglycemia